2015
DOI: 10.4238/2015.december.28.31
|View full text |Cite|
|
Sign up to set email alerts
|

Association between TAP1 gene polymorphisms and alopecia areata in a Korean population

et al.

Abstract: ABSTRACT. The transporter 1 ATP-binding cassette sub-family B (MDR/ TAP) gene (TAP1) is located in the major histocompatibility complex class 18821 TAP1 polymorphisms and alopecia areata ©FUNPEC-RP www.funpecrp.com.br Genetics and Molecular Research 14 (4): 18820-18827 (2015) II region, and forms a heterodimer that plays a key role in endogenous antigen presentation pathways. Investigation of polymorphisms identified in these loci has revealed an association with several autoimmune disorders. Alopecia areat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It has been proposed that TAP gene may be responsible for atopic disease susceptibility. Polymorphisms in TAP1 may affect antigen recognition and presentation, potentially resulting in low expression or entirely absence of MHC-I at the cell surface, which could ultimately lead to an adverse immune response [ 4 ]. Studies on the polymorphisms of the TAP1 gene in several human leukocyte antigen (HLA)-associated diseases such as atopic dermatitis, asthma, rhinitis [ 5 – 14 ] found that rs1057141 and rs1135216 as the most common single nucleotide polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that TAP gene may be responsible for atopic disease susceptibility. Polymorphisms in TAP1 may affect antigen recognition and presentation, potentially resulting in low expression or entirely absence of MHC-I at the cell surface, which could ultimately lead to an adverse immune response [ 4 ]. Studies on the polymorphisms of the TAP1 gene in several human leukocyte antigen (HLA)-associated diseases such as atopic dermatitis, asthma, rhinitis [ 5 – 14 ] found that rs1057141 and rs1135216 as the most common single nucleotide polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…The MHC class I complex consists of three main subunit structures, which together enable the escape of immune proteins from the endoplasmic reticulum (ER) to the cell surface. The complex includes the ATP-binding cassette transporter (TAP), ERp57, and MHC class I molecules (30)(31)(32). TAP belongs to a large family of ATP-binding cassette transporters and is composed of the TAP1 and TAP2 subunits (33).…”
mentioning
confidence: 99%
“…Investigation of polymorphisms in TAP1 identified an association with several autoimmune diseases and AA is one of them 28. The study of Kim et al was one of the first documented studies in comparing genotypic and allelic frequencies of TAP1 in patients with AA 28.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of polymorphisms in TAP1 identified an association with several autoimmune diseases and AA is one of them 28. The study of Kim et al was one of the first documented studies in comparing genotypic and allelic frequencies of TAP1 in patients with AA 28. In their study, Korean patients were tested for three selected SNPs (rs2071480, rs1135216, and rs1057141), whereas results suggested an association of a promoter SNP (rs2071480) in the heterozygous G/T co-dominant.…”
Section: Discussionmentioning
confidence: 99%